A Simplified Method for Pore Pressure Buildup Prediction: From Laboratory Cyclic Tests to the 1D Soil Response Analysis in Effective Stress Conditions. (2016) - Chiaradonna, Anna; Tropeano, Giuseppe; d'Onofrio, Anna; Silvestri, Francesco
Abstract: The importance of predictions of earthquake-induced pore water pressure has been widely recognized for reliable evaluations of strong-motion response of saturated soil. The build-up of excess pore water pressure, in fact, causes reduction in soil stiffness and strength, in some cases leading to liquefaction. Simplified predictive models in the literature are empirically based on the results of cyclic laboratory tests carried out in strain- or stress-controlled conditions. Most of such empirical models require, preliminarily, that the irregular earthquake load is reduced to an equivalent number of cycles of uniform shear stress, in order to reproduce the effect of a laboratory cyclic test. To avoid such conversion, rather complex and not always reliable, a stress-based model is here proposed that allows for the direct generalization of the cyclic test data to irregular stress histories. More realistic predictions should take into account also the dissipation and redistribution of pore pressure within a soil deposit, which can be effectively modelled using the one-dimensional theory of consolidation. The build-up and dissipation models have been incorporated in a program for 1D seismic response analyses in the time domain, in order to carry out coupled dynamic analyses in terms of effective stress. In this paper, after a brief recall of the proposed PWP model, the code performance will be verified with reference to a case history of a dyke damaged during the seismic sequence occurred in Emilia plain (Italy) in May, 2012.